INCREASING THE STUDENTS’ SPEAKING ACHIEVEMENT BY APPLYING PICTURE STORY GAME OF GRADE X - wiki tedi rahmawati; Sahla Rizqina; Iskandar Zulkarnain (EXCELLENCE: Journal of English and English Education, 2022)
This research aimed to elaborate the increasing students’ speaking achievement using picture story game. The research design applied was classroom action research. There were two cycles conducted to accomplish this research. Each cycle was conducted through four phases. The subject was all students of grade X with total number of 30 students. The instruments used for collecting data were speaking test, observation sheet, diary notes, and interview sheets. The techniques for collecting data were orientation test and treatment by teaching the students using picture story game. Data analysis showed that in quantitative data, the mean score obtained in orientation test was 42.6 and none of the students achieved equal or higher than 75 as the passing grade score. In 1st meeting of Cycle I the mean score was 45.6 or 0% of the total students got >75. In 2nd meeting of Cycle I the mean score improved to 54.4 with 2 students (6.66%) obtained score >75. In the 1st meeting Cycle II the mean score kept improving to 72.0 with 14 students (46.66%) got >75. In 2nd meeting of Cycle II the mean score improved significantly to 87.0 with 28 students (93.33%) got >75. The improvement could be seen through the activity in each cycle. Thus, it is concluded that the picture story game increased the students’ achievement in speaking of grade X students.